Holding Foreign Insiders Accountable - Jackson, Robert; Lynch-Levy, Bradford; Taylor, Daniel (Management Science, 2024)
Whereas corporate insiders at U.S.-listed, U.S.-domiciled companies must disclose their stock sales electronically within two business days on Form 4, the U.S. Securities and Exchange Commission (SEC) exempts insiders at U.S.-listed, foreign-domiciled companies from this requirement. Instead, these “foreign insiders” report their sales on a paper form mail-filed with the SEC. Using a unique data set compiled from digitized versions of thousands of paper forms, we examine the stock sales of foreign insiders and compare their trading to that of their U.S. counterparts. Consistent with a lack of public scrutiny facilitating opportunism, we show that foreign insiders’ stock sales are highly opportunistic and opportunistic trading is concentrated in companies that are domiciled in nonextradition countries beyond the reach of U.S. legal authorities: specifically, Russia and China. The average stock sale by foreign insiders affiliated with companies domiciled in these countries is more than four times larger than that of U.S. insiders and occurs prior to stock price declines of at least −18%. In our sample, we estimate that insiders at these companies have traded to avoid losses of more than $9 billion. Collectively, our results suggest that corporate insiders associated with Chinese and Russian companies listed on U.S. exchanges trade in a highly opportunistic and abusive manner. The SEC’s decision to exempt these insiders from Form 4 reporting requirements prevents much needed public scrutiny of their trading and, in turn, prevents market forces from disciplining their trading. This paper was accepted by Suraj Srinivasan, accounting. Funding: We thank our schools and the Dean’s Research Fund at Wharton for financial support. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2022.02131 .